Penerapan Permainan Edukatif Ular Tangga Siaga Bencana Untuk Meningkatkan Pengetahuan Pendidikan Kebencanaan Anak Usia Dini di Kabupaten Magelang - Purwati, Purwati; Rahmawati, Siti Azizah; Japar, Muhammad; Nikmah, Filda Khoirun; Nurrohmah, Ananda Putri; Asih, Susmawati Surya (AWLADY : Jurnal Pendidikan Anak, 2024)
Snakes and Ladders Early Childhood Disaster Alert is an Educational Game Tool (APE) that can be played by two or more children. Snakes and Ladders Early Childhood Disaster Alert was created with the aim of assisting parents and educators in conveying preparedness to early childhood to know and learn about disaster education. Snakes and Ladders Disaster Alert is designed for children aged 3-6 years who in their games require a variety of activities both activities related to motor, cognitive, social, and language. Snakes and Ladders Disaster Alert in large sizes and made of materials that are safe for children. Snakes and Ladders Early Childhood Disaster Alert contains content that can educate children about types of disasters, how to deal with disasters, self-rescue and how to prevent disasters both due to natural and human factors. In its implementation, Snakes and Ladders for Early Childhood Disaster Alert requires the assistance of teachers or parents so that the content can be conveyed properly by children.Keywords: Snakes and ladders, disasters, education, early childhood